DESAIN MODEL PEMBELAJARAN ONLINE SEBAGAI UPAYA MEMFASILITASI BELAJAR DI TEMPAT KERJA - Meisa Diningrat, Syaiputra Wahyuda (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2019)
Vocational high school in Indonesia is familiar with the concept of dual system education program. There are two places of learning such as school-based learning and work-based learning. A few vocational education institutions have claimed that during carry out work-based learning, they ask students to master some competencies through self-regulated learning without a learning environment that planned. Therefore, this article aims to give an integrative learning design framework for online learning as an effort to guide educators and instructional designers in designing and developing online learning environment that meet with the students need. Shifting roles of educators and instructional designers in online learning, each component within integrative learning design framework for online learning, as well as the features of online learning model are discussed here. So that, educators and instructional designers who want to design online learning model could not only avoid mistakes but also reduce the failure.